2008
DOI: 10.1039/b719789f
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic, electrochemical and computational study of Pt–diimine–dithiolene complexes: rationalising the properties of solar cell dyes

Abstract: A series of [Pt(ii)(diimine)(dithiolate)] complexes of general formula [Pt{X,X'-(CO(2)R)(2)-bpy}(mnt)] (where X = 3, 4 or 5; R = H or Et, bpy = 2,2'-bipyridyl and mnt = maleonitriledithiolate), have been spectroscopically, electrochemically and computationally characterised and compared with the precursors [Pt{X,X'-(CO(2)R)(2)-bpy}Cl(2)] and X,X'-(CO(2)R)(2)-bpy. The study includes cyclic voltammetry, in situ EPR spectroelectrochemical studies of fluid solution and frozen solution samples, UV/Vis/NIR spectroel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
37
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(40 citation statements)
references
References 32 publications
3
37
0
Order By: Relevance
“…The presence of the solvent molecules completely changes the crystal packing of (3) from that in (2). Indeed, the core molecules in (3) form Pt2ÁÁÁPt1ÁÁÁPt1AÁÁÁPt2A intermolecular contacts with alternating distances 3.501, 3.431, 3.501 Å , respectively, forming infinite chains along the b axis (Fig.…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…The presence of the solvent molecules completely changes the crystal packing of (3) from that in (2). Indeed, the core molecules in (3) form Pt2ÁÁÁPt1ÁÁÁPt1AÁÁÁPt2A intermolecular contacts with alternating distances 3.501, 3.431, 3.501 Å , respectively, forming infinite chains along the b axis (Fig.…”
Section: Resultsmentioning
confidence: 96%
“…4). These contacts manifest weak metallophilic (platinophilic in particular) pairwise interactions as the second type of supramolecular interactions in (2). In addition to platinum atom contacts, weak intermolecular C-HÁÁÁO hydrogen bonds link molecules A and B with almost orthogonal orientation as dimers ( Fig.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…In a later study [17] the superior performance of the 3,3'-bipyridyl complex was rationalized by using density functional theory calculations based on a hybrid functional that suggested that the longer-lived charge-separated state for this complex on TiO 2 was related to the non-planar geometry of the complex, reducing the electronic coupling between ligands. Lazarides et al [18] have attempted to increase the light absorption properties of Pt(II)(diimine)(dithiolate) chromophores by combining them with boron-dipyrromethene, a strongly absorbing dye, in a dual chromophore system.…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, square-planar complexes with sulfur-containing ligands that absorb in the near infrared region (NIR) of the spectrum have attracted special interest and have been examined both experimentally and theoretically [12,15,16,17,18,19].…”
Section: Introductionmentioning
confidence: 99%